2020
DOI: 10.3389/fpsyg.2020.02127
|View full text |Cite
|
Sign up to set email alerts
|

Digital Learning Games for Mathematics and Computer Science Education: The Need for Preregistered RCTs, Standardized Methodology, and Advanced Technology

Abstract: In today's digital information society, mathematical and computational skills are becoming increasingly important. With the demand for mathematical and computational literacy rising, the question of how these skills can be effectively taught in schools is among the top priorities in education. Game-based learning promises to diversify education, increase students' interest and motivation, and offer positive and effective learning experiences. Especially digital game-based learning (DGBL) is considered an effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 109 publications
1
18
0
Order By: Relevance
“…Qualitatively, children reported that the game Entropy Mastermind was fun, and their verbal reports give evidence that the game fostered their intuitions about entropy: students repeatedly asked whether they could play the game again. This observation corroborates the finding in the literature that students enjoy gamified learning experiences (Bertram, 2020) and suggests that games can foster intuitive understanding of abstract concepts such as mathematical entropy. It is remarkable that we found this positive learning outcome in elementary school students, whose mathematical proficiency was far from understanding formulas as abstract as mathematical entropy at the time of data collection.…”
Section: Discussionsupporting
confidence: 90%
“…Qualitatively, children reported that the game Entropy Mastermind was fun, and their verbal reports give evidence that the game fostered their intuitions about entropy: students repeatedly asked whether they could play the game again. This observation corroborates the finding in the literature that students enjoy gamified learning experiences (Bertram, 2020) and suggests that games can foster intuitive understanding of abstract concepts such as mathematical entropy. It is remarkable that we found this positive learning outcome in elementary school students, whose mathematical proficiency was far from understanding formulas as abstract as mathematical entropy at the time of data collection.…”
Section: Discussionsupporting
confidence: 90%
“…Well designed, the games provide interactive, playful learning environments that facilitate the acquisition of self-directed skills by students [68], improve motivation, and reduce anxiety associated with learning mathematics [69]. With appropriate pedagogical criteria and the guidance of the mathematics teacher, gamification can significantly impact students' mathematical learning [70].…”
Section: Gamificationmentioning
confidence: 99%
“…In the didactics of mathematics, most educational games focus on operations with numbers, algebra, geometry, measurement, data analysis, and probability [46]. Although the number of educational digital games for math learning [24] and programming [72] is significant, evidence-based digital learning games for science in elementary and secondary education are scarce [66,68]. Studies support their use in the classroom depending on the available ICT resources [73,74].…”
Section: Gamificationmentioning
confidence: 99%
See 2 more Smart Citations